Context, Resources and Strategic Choice: Responses to Labour and Skill Shortages - Lavelle, Jonathan; Ryan, Lorraine; O’Sullivan, Michelle; Murphy, Caroline; MacMahon, Juliet; Dundon, Tony (Relations industrielles / Industrial Relations, 2025)
SummaryLabour and skill shortages are widely reported across most countries. With changing demographics, increasing digitalization and the transition to a green economy, to name but a few factors, concern is mounting about the supply of labour and skills for future demands. As a result, actors in the labour market, such as unions, employers and employer associations, government and civil society organizations are concerned about looming shortages of labour and skills. Several strategies to address such shortages have been identified, but a more detailed engagement is required to fully understand the complex interplay between each strategy and the environment in which it is pursued. Semi-structured interviews were conducted in Ireland with a range of actors who were specifically identified as having expertise and experience in strategies for labour and skill shortages. They reported a range of strategies that involved upskilling, higher pay, better working conditions, flexible work arrangements, use of migrant labour, development of untapped labour pools and provisioning of social goods. Decisions on these strategies had two key determinants: resource availability and the external environment. All actors mentioned a need for social dialogue to engage, explore and consider the wide range of options for dealing with labour and skill shortages.